Cardiovascular Benefits With Favorable Renal, Amputation and Hypoglycemic Outcomes of SGLT-2 Inhibitors in Type 2 Diabetes From the Asian Perspective: A Population-Based Cohort Study and Systematic Review - Yang, Chun-Ting; Peng, Zi-Yang; Chen, Yi-Chi; Ou, Huang-Tz; Kuo, Shihchen (Frontiers in Endocrinology, 2022)
Objective We assessed the effects of sodium glucose cotransporter-2 inhibitors (SGLT2is) versus dipeptidyl peptidase-4 inhibitors (DPP4is) in a large real-world Asian cohort with type 2 diabetes (T2D) and performed a systematic review with integrating the present study findings to provide up-to-date evidence from the Asian perspective. Methods New users of SGLT2is or DPP4is were identified from the Taiwan’s National Health Insurance Research Database and followed until 2018. Primary outcomes were hospitalization for heart failure (HHF) and three-point major adverse cardiovascular event (3P-MACE; namely, myocardial infarction [MI], stroke, or cardiovascular death). Other outcomes included all-cause death, chronic kidney disease (CKD), amputation, and hospitalized hypoglycemia. Subdistribution hazard models were employed to assess treatment-associated clinical outcomes. Results A total of 21,329 SGLT2i and DPP4i propensity-score-matched pairs were analyzed. SGLT2is versus DPP4is showed lower risks of HHF (hazard ratio [95% CI]: 0.52 [0.45–0.59]), 3P-MACE (0.62 [0.55–0.70]), MI (0.63 [0.50–0.79]), stroke (0.60 [0.51–0.70]), all-cause death (0.57 [0.49–0.67]), CKD (0.46 [0.43–0.50]), amputation (0.64 [0.42–0.98]), and hospitalized hypoglycemia (0.54 [0.45–0.64]). Our results were consistent with findings from a systematic review. Conclusion Among Asian patients with T2D, SGLT2is versus DPP4is showed benefits for several clinical outcomes. More research is warranted to explore the heterogeneous treatment effects of SGLT2is and DPP4is by race/ethnicity.